2017
DOI: 10.1021/acs.accounts.6b00630
|View full text |Cite
|
Sign up to set email alerts
|

Practical Stereochemistry

Abstract: The relationship between fundamental and applied is often uneasy, particularly in modern political climates. A familiar political view, aimed negatively at the scientific community, is that the former is a waste of money whereas the latter gives value for investment. The answer that fundamental is required as the basis for practical suffers from the fact that the timelines between fundamental and practical are often long and the routes contorted and unexpected. This has been my experience. In this Account, exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…The elaborations of some enantioenriched thiiranes were also carried out. Unfortunately, it was found that tetrasubstituted alkenes D1 – D4 via desulfuration of thiirane C1 or C33 , namely Barton–Kellogg olefination, [4c, 14] were afforded in decent results under varied conditions (Scheme 2c, see the Supporting Information for details). These results indicate that the high tense strain of the 3‐membered ring of thiirane was more likely to be released via desulfuration, [4c, 6] rather than substitution reaction, ring opening or expansion [15] .…”
Section: Resultsmentioning
confidence: 99%
“…The elaborations of some enantioenriched thiiranes were also carried out. Unfortunately, it was found that tetrasubstituted alkenes D1 – D4 via desulfuration of thiirane C1 or C33 , namely Barton–Kellogg olefination, [4c, 14] were afforded in decent results under varied conditions (Scheme 2c, see the Supporting Information for details). These results indicate that the high tense strain of the 3‐membered ring of thiirane was more likely to be released via desulfuration, [4c, 6] rather than substitution reaction, ring opening or expansion [15] .…”
Section: Resultsmentioning
confidence: 99%
“…Resolution via diastereomeric salt formation is a classical method which is becoming somewhat neglected partly due to the development of new routes to efficient asymmetric syntheses with enantiomeric control such as organocatalysis . However, the combined use of powder diffraction and modern single crystal X‐ray structure determination can be of value in understanding the mechanism of resolution and in identifying the issues when such resolutions are not fully efficient.…”
Section: Discussionmentioning
confidence: 99%
“…When particular crystallization methods, e.g. seeding crystallization with the desired homochiral crystal, the achiral starting compound can be selectively transformed into only one of the enantiomorphous crystals [126]. This method enables the controlled preparation of one desired enantiomer.…”
Section: Chiral Induction In Crystalsmentioning
confidence: 99%